Bronchogenic cyst: a rare case of malignant transformation. Issue 4 (4th April 2022) - Whooley, Jack; White, Alexandra; Soo, Alan
Abstract : Bronchogenic cysts are rare cystic malformations of the respiratory tract with prevalence that is largely unknown. They are most commonly diagnosed incidentally in asymptomatic patients. While surgical resection is the mainstay of treatment for patients who are symptomatic, the treatment course for patients without symptoms is less clear. We describe the case of an initially asymptomatic elderly man who was found to have a bronchogenic cyst on routine surveillance imaging, culminating in the rapid enlargement and malignant transformation of the cyst, ultimately resulting in a technically difficult and challenging surgical resection. The malignant transformation of these bronchogenic cysts is exceedingly rare, with only a few well-documented cases reported in the literature. To our knowledge, this is the first report of a squamous cell carcinoma arising from a bronchogenic cyst in the paratracheal region.